The Crisis of African (Nigeria) Leadership and Development: A Trans-colonial Analysis - Michael Okeke, Nmesoma (Cultural Conflict and Integration, 2025)
This essay contends that poor leadership results in poor development outcomes, whereas ethical leadership facilitates sustainable development, the hallmark of forward-thinking nations. The crisis of leadership in Africa remains central to understanding the continent’s developmental challenges. Too often, leadership has produced individuals lacking agential integrity, thereby weakening the continent’s global standing. Historically, African development has been analyzed through colonial and postcolonial lenses; however, this essay adopts a trans-colonial approach as a constructive framework for leadership transformation and societal advancement. We argue that development is not a passive invitation but an intentional and conscious commitment driven by visionary leadership. This work contends that leadership either ignites or cripples national development. To support this claim, a case study of Nigeria’s leadership trajectory since 1999 will be used to demonstrate how poor leadership results in a disjointed and fragile developmental structure. From a trans-colonial standpoint, leadership must become the spark that activates a zealous love for Africa, expressed in creative and critical ways. We conclude that Africa needs visionary leaders who will catapult and pilot her affairs to the next level. Thus, this essay reimagines leadership as the foundation upon which transformative, humane, and sustainable development must be built.